Processing Village Superior Commodities Into Competitive Multisrata Products in West Halmahera District - Sinyo, Yumima; Tolangara, Abdurasyid; Sundari, Sundari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research analyzes superior commodities and their derivative products (multistrata products) in West Halmahera Regency, North Maluku Province. The study was conducted in Golo village, Sahu sub-district from March to August 2024, using both quantitative and qualitative methods. Data collection involved primary sources through field surveys and secondary sources from government agencies. Location Quotient (LQ) analysis revealed banana (1.562), coconut (1.544), nutmeg (1.243), and corn (1.240) as base sector commodities, while durian (0.116) was identified as a non-base sector commodity.